NETRALITAS APARATUR SIPIL NEGARA DALAM PEMILIHAN GUBERNUR DAN WAKIL GUBERNUR PROVINSI JAWA TENGAH TAHUN 2024 - Intan Nur’aini; Nur Hidayat Sardini (Journal of Politic and Government Studies, 2026)
Civil servants (ASN) are a crucial component of the government structure, playing a strategic role as implementers of public policy, providers of public services, and as a unifying force for the nation. Therefore, the professionalism and neutrality of ASN are crucial aspects in carrying out these functions and duties. This research is motivated by the frequent violations of ASN neutrality in political contests, particularly during regional elections (Pilkada). The theoretical foundations used to analyze this phenomenon are the theory of bureaucratic neutrality and the theory of patron-client relations. The research method used is descriptive qualitative, aiming to describe in detail the reality, particularly regarding the dynamics of ASN behavior and efforts to enforce neutrality by relevant institutions in the 2024 Central Java gubernatorial election. Data collection techniques were conducted through interviews and documentation studies. The results of this study indicate that violations of ASN neutrality continue to occur. Based on data from the Central Java Provincial Elections Supervisory Agency (Bawaslu), two ASNs were found to have violated neutrality, one in Sukoharjo Regency. This is despite efforts to enforce neutrality, starting from pre-election (socialization and prevention), the election period (supervision), and post-election (sanction enforcement). This study also identified several factors causing ASN's lack of neutrality and obstacles in the process of handling neutrality violations. The study's conclusions indicate a gap between public perception and official Bawaslu data. Based on interviews with several voters, the public still frequently encounters ASN who show bias towards certain candidates. However, the number of violations officially recorded by Bawaslu is relatively small or low, namely only two cases. This indicates a gap between field practices and formal reporting. Therefore, this study recommends several steps, namely: 1) increasing ASN's understanding of the principle of neutrality, 2) strengthening inter-agency coordination, 3) increasing the commitment of PPK, and 4) evaluating and adjusting regulations related to ASN neutrality.